Analisis Struktural Surah Al-Mâ‘Ûn - Solahuddin, Ahmad (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2016)
QS. al-Mâ‘ûn was seen as likely incoherent for the structural sura has definitely talking on some topics. This article would analyze QS. al-Mâ‘ûn by using semiotics approach with operational steps: giving analysis on the level (1) syntagmatic, (2) paradigmatic, (3) binary opposition, (4) historical confirmation. In the end, the results show that: first, QS. al-Mâ‘ûn has the cohesiveness of the structure shown by the existing cohesive element. The relationship between the first and the second verses is shown by fâ’ fa?î?ah. The relationship between verses 2 and 3 is shown by waw ‘a?f. The relationship between verse 4 and the previous verse, (QS. al-Mâ‘ûn: 1, 2 and 3) is indicated by fâ’ fa?î?ah; or may be it says that the fourth verse is the answer to the question of the first verse. Then, between verse 4, 5 and 6, is actually a sentence. While the relationship between verse 7 with the previous verse (QS. al-Mâ‘ûn: 4, 5 and 6) is shown by waw ‘a?f. Second, QS. al-Mâ‘ûn speaks about religious liar who is characterized: 1. A person who likes to be harsh on orphans and forbidding to feed the poor, 2. People who are lax in prayer and have no social concern.